2005
DOI: 10.1111/j.1468-2982.2004.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Symptomatic Treatments on Cutaneous Hyperalgesia and Laser Evoked Potentials During Migraine Attack

Abstract: Previously an amplitude enhancement of laser evoked potentials (LEPs) was detected during migraine attack: we further examined pain threshold to CO2 laser stimuli and LEPs during attacks, evaluating the effect of almotriptan, lysine-acetylsalicylate and placebo treatment on cutaneous hyperalgesia to thermal stimuli delivered by CO2 laser and on LEP components. Eighteen patients suffering from migraine without aura were analysed. They were divided into three groups of six patients each, randomly assigned to lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
0
19
0
5
Order By: Relevance
“…Similarly, in a study on acute therapies for migraine attack, we observed no drug-induced effects on laser pain concomitant with the clear inhibition of laser-evoked responses [23]. This apparent contrast may be supported by the principle that LEPs reflect more the status of sensory pathways than the perception of subjective pain [8], despite a linear correlation between the intensity of pain perception and the amplitude of vertex LEPs is often present [24].…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, in a study on acute therapies for migraine attack, we observed no drug-induced effects on laser pain concomitant with the clear inhibition of laser-evoked responses [23]. This apparent contrast may be supported by the principle that LEPs reflect more the status of sensory pathways than the perception of subjective pain [8], despite a linear correlation between the intensity of pain perception and the amplitude of vertex LEPs is often present [24].…”
Section: Discussionmentioning
confidence: 52%
“…16,20 All of them could contribute to central pain in patients with PD in the context of enhanced LEPs, although higher attention toward the stimulated limb usually leads to asymmetric LEPS, which seems not to be the case of our patients. 20 The decrement of LEP amplitude caused by L-dopa intake in our PD-PCP patients is not a definitive proof for the involvement of dopamine in pain perception, as suggested by previous studies, 5,31 because similar effects have been described for analgesic drugs, 32,33 or even placebo. 34 However, our patients showed higher pain thresholds and lower subjective perception of ongoing pain in "on" condition.…”
Section: Discussionmentioning
confidence: 73%
“…During migraine attacks, the area-under-the-curve of the nociceptive blink reflex R2 component is temporary increased on the affected side in comparison with the non-affected side was observed [106]. Similar results were obtained using another noxious stimulation, the radiant laser CO2: amplitude of the N2–P2 complex at the vertex was increased on the affected side compared to the non-affected side [107-109]. Interestingly, in episodic migraine LEPs did not habituate not only interictally, but also during the attacks, underscoring the different cerebral processing of noxious versus innocuous stimuli.…”
Section: Reviewmentioning
confidence: 69%